Physiological and anatomical responses of Passiflora tripartita var. mollissima (Passifloraceae) in water deficit - Toro-Tobón, Gabriela (2024)
Introduction: Passiflora tripartita var. mollissima (banana passionfruit) is one of the most promising exotic tropical fruits from the diversity of the Passifloraceae family in South America, because of its organoleptic properties and antioxidant activity. Objective: To evaluate the physiological and anatomical responses of banana passionfruit plants under water deficit to better understand the mechanisms that mitigate this stress and affect the production of crops subject to climate change and global warming. Methods: Three-month-old seedlings of banana passionfruit were subjected to a soil water deficit through an irrigation reduction at 70 % for 49 days under greenhouse conditions. Morphology (leaf area, height, and number of leaves) and physiological (stomatal conductance, Fv/Fm, total chlorophyll content) measurements were made through time, and after the irrigation treatments were measured biomass parameters and anatomical foliar traits. Results: The plants experienced a decrease in height, leaf area, number of leaves, leaf area index, and relative water content, that are common responses in plants subjected to reduced irrigation. Additionally, the plants exhibited certain mechanisms that can be attributed to water deficit tolerance such as higher root: shoot ratio, stomatal closing, an increase in stomatal density, a reduction in mesophyll tissue thickness, and a decrease in the number of vessels and its diameter as they enable the banana passionfruit to reduce water loss and decrease the probability of cavitation in xylem vessels. Conclusions: banana passionfruit plants could implement strategies against water scarcity, allowing them to survive and endure challenging environmental conditions